Distribution of cephalopod paralarvae across the Florida Current front in the Florida Keys: preliminary results - Goldman, David A. (1993)
In this communication I present the preliminary results of a study which will quantitatively describe the paralarval cephalopod as semblages across the FC front off the Florida Keys utilizing multivariate data. Results of this work will help determine the ecological significance of the Florida Current front to paralarval cephalopods.